Conceptualizing vegetation in the Bantu Expansion: Reflections on linguistics in central African history. (20th August 2017) - de Luna, Kathryn M.
Abstract: The state of linguistics research on human settlement in central Africa suggests that rainforest environments were undesirable locations for settlement for many of the early speech communities associated with the extension of Bantu-speaking populations and languages into the region. Explanations for this preference tend to focus on the presumed challenge of adapting the earliest Bantu savanna subsistence system to the new rainforest environment. Recent syntheses incorporating linguistic, archaeological, and paleoclimatic evidence argue that periods of climate change encouraged the growth of wooded savanna, secondary forest, and grasslands at the margins and even in heart of the rainforest; these more open environments may have facilitated the expansion of Bantu languages into the through central Africa. A re-analysis of three previously proposed lexical reconstructions, however, reveals that early Bantu words for generic forms of vegetation (forests, thickets, trees, and the bush) offer key insights into the changing ways that Bantu speakers conceptualized and valued uninhabited spaces and areas of dense vegetation even as the majority of Bantu speakers elected to settle within intercalary zones of wooded savanna, secondary forest, and grasslands located throughout the rainforest.